Progression free survival and functional outcome after surgical resection of intramedullary ependymomas. Issue 12 (December 2015) - Abdullah, Kalil G.; Lubelski, Daniel; Miller, Jacob; Steinmetz, Michael P.; Shin, John H.; Krishnaney, Ajit; Mroz, Thomas E.; Benzel, Edward C.
Abstract: We present a 15 year institutional analysis of the factors affecting progression free survival (PFS) and overall survival (OS) in patients undergoing attempted resection of adult intramedullary spinal cord ependymomas. Intramedullary spinal cord tumors are rare but important clinical entities, and ependymomas are the most commonly encountered intramedullary tumor. In total, 53 adult patients over the span of 15 years were analyzed for OS, PFS, and the effects of plane of dissection (POD) and gross total resection (GTR) on functional and long term outcomes. The mean age was 45 years and median follow-up was 54 months. The follow-up neurological outcome and modified McCormick scale were used to determine the functional outcome. Kaplan–Meier curves were used to calculate progression and survival. The overall ability to achieve GTR was significantly correlated to identification of an intraoperative POD ( p  < 0.001). There was a trend towards increased PFS with the ability to achieve a GTR. There was no significant difference in the pre- and postoperative functional outcome scores. The ability to achieve a GTR is strongly correlated to the identification of a POD in ependymomas. There is a trend towards an increased probability of PFS in intramedullary spinal cord tumors when GTR is achieved. The resection of these tumors is likely to halt, but not reverse, neurological deterioration.